Integrity of the yeast mitochondrial genome, but not its distribution and inheritance, relies on mitochondrial fission and fusion - Osman, Christof (Proc Natl Acad Sci U S A, 2015)
Mitochondrial DNA (mtDNA) is essential for mitochondrial and cellular function. In Saccharomyces cerevisiae, mtDNA is organized in nucleoprotein structures termed nucleoids, which are distributed throughout the mitochondrial network and are faithfully inherited during the cell cycle. How the cell distributes and inherits mtDNA is incompletely understood although an involvement of mitochondrial fission and fusion has been suggested. We developed a LacO-LacI system to noninvasively image mtDNA dynamics in living cells. Using this system, we found that nucleoids are nonrandomly spaced within the mitochondrial network and observed the spatiotemporal events involved in mtDNA inheritance. Surprisingly, cells deficient in mitochondrial fusion and fission distributed and inherited mtDNA normally, pointing to alternative pathways involved in these processes. We identified such a mechanism, where we observed fission-independent, but F-actin–dependent, tip generation that was linked to the positioning of mtDNA to the newly generated tip. Although mitochondrial fusion and fission were dispensable for mtDNA distribution and inheritance, we show through a combination of genetics and next-generation sequencing that their absence leads to an accumulation of mitochondrial genomes harboring deleterious structural variations that cluster at the origins of mtDNA replication, thus revealing crucial roles for mitochondrial fusion and fission in maintaining the integrity of the mitochondrial genome.